Writing successful reports and dissertations - Becker, Lucinda M. (Sage study skills.)
"Help is here! In this handy little book you will find expert guidance to enable you to produce a successful report or dissertation. With a focus on developing an effective writing style and argument, this book will show you, step-by-step, how to plan and deliver a perfect piece of writing to gain top marks."--Page [4] of cover.